A test of self-determination theory with wheelchair basketball players with and without disability - Perreault, S.; Vallerand, R. J. (Adapted Physical Activity Quarterly, 2007)
Guided by Self-Determination Theory (SDT), the present study examined the sport motivation and coping skills of male and female wheelchair basketball players with and without disability (N = 72). In line with SDT, results showed that intrinsic and extrinsic motivation as well as amotivation was found to be present in this sample of wheelchair basketball players. Results also demonstrated that the participants surveyed in the present study scored higher on self-determined types of motivation than non self-determined types of motivation, thus replicating past research with athletes without disability. Furthermore, wheelchair basketball players with and without disability did not differ significantly with respect to sport motivation and coping skills, suggesting that they are more alike than dissimilar. Finally, results revealed that self-determined motivation is associated with enhanced psychological functioning.